RITUAL USING DAN JAWA: MITOS HIBRIDITAS BUDAYA SEBAGAI INTEGRASI DAN HARMONI SOSIAL - Titik Maslikatin; Novi Anoegrajekti; Sudartomo Macaryus (Faculty of Humanities, Jember University, 2015)
This paper aims to find a migration culture that looks at the rites as a manifestation of the religiosity of society. This is expressed in various ways, according to the natural environment, social customs and community supporters. Data were analyzed by using an ethnographic method. A literature study was followed by field research. Meaning was done by looking at the relationship among the data to get a comprehensive conclusion. The results showed that Banyuwangi seblang and Nini Thowong of Yogyakarta rooted in rural agrarian culture. It looks at the materials, accessories, and the content of the songs used to accompany the dance movements of both. The differences of the two dances are as follow. Seblang perpetrators are women, and become a rite that was placed as part of a cleansing ceremony of the village, and the time and place are determined by custom implementation. Nini Thowong performance with actors as a transfer media of female doll spirit is a tradition art to entertain. Therefore, time and venue are adapted to responders’ request.Keywords: village cleansing, entertainment, religiosity, rites